A shared reflection report from award recipients at the European Health Psychology Society Conference 2025 - Madeleine Warmer; Jennifer Tows; Lucia Volpi; Valentina Rossi; Abdulmalik Yemi Olaosebikan; Brona Mulligan; Dario Leanza; Rebecca Trower; Lucia Kupkovicova; Marina Hinssen; Ivana Ivancic; Mariana Brazão (European Health Psychologist, 2026)
In August 2025, the 39th Annual Conference of the European Health Psychology Society brought us together in Groningen, Netherlands, with more than 800 academics, researchers, students, and practitioners from over 50 countries participating. This year’s conference theme was “Putting Health Psychology to Work: Prevention, Practice, Policy”, focusing on the application of health psychology in practice and bridging the research with real-world practice. This reflection report, written from the perspective of conference grant award recipients, aims to provide insight into the experience of attending EHPS for early career researchers, future attendees, and prospective applicants. We reflect on key aspects of the conference, including participation in the CREATE workshop on open science, engagement with the scientific programme, and opportunities for networking and professional development. We were selected for these awards based on the relevance and quality of our ongoing research in health behaviour and intervention development, as well as our contribution to the conference programme. Receiving the conference grants allowed us to attend and fully engage with the event, including participation in the CREATE workshop on open science, with a particular focus on preregistration and registered reports. We highlight how the CREATE workshop supported the development of practical open science skills, how the scientific programme encouraged critical reflection on translating research into practice, and how informal and structured networking opportunities nurtured a strong sense of community within the field. Overall, this report outlines not only what we learned but also how the conference contributed to our development as early-career researchers within health psychology.